Methods of multivariate data analysis in insects synecology - Sushko, Gennadi G. (Journal of the Belarusian State University. Ecology, 2020)
Analysis of publications on insect ecology over the past five years, available in the international database PubMed Central, showed that 65,6 % of them contain ordination methods. This emphasizes their relevance at the present stage. These methods allow to select groups with common properties, identify gradients and trends in multivariate data, demonstrate the relationships among variables and determine which of them are the most influential. This article provides a brief overview of the methods of ordination, most often used in environmental studies of insects and identifies restrictions on their use.
Keywords: Multivariate analysis; ordination; entomology; community ecology